Pengaruh Return On Equity, Earning Per Share Dan Price Earning Ratio Terhadap Harga Saham Price Book Value: (Pada Perusahaan Property Dan Real Estate Yang Terdaftar Di BEI Periode 2016 -2020) - Suharna; Syamsuri (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Background: In 2020, almost all companies in the property sub-sector had the impact of decreasing people's purchasing because of the spread of the COVID-19 pandemic. Since the pandemic Covid-19 in Indonesia start in March 2020, absorption and sales have fallen drastically. Since 2017 there has been decreasing in sales in the property and real estate sub-sector, followed by share prices in the Property & Real Estate sub-sector. Purpose: This study was conducted to find out empirical evidence of the effect of ROE, EPS, and PER on Stock Prices (Price Book Value) in Property and Real Estate Sub-Sector Companies listed on the Indonesia Stock Exchange. Methods: This study uses secondary data for the period 2016 – 2020 obtained from annual financial reports published on the IDX website and website (internet). Results: based on the hypothesis, multiple linear regression was used by looking at the value of the t-statistical test. Based on the results of hypothesis testing, it was found that ROE, EPS and PER have an effect on Price Book Value (PBV). Conclusion: Based on this research, the variables of ROE, EPS, and PER simultaneously have an effect on increasing the Price Book Value (PBV).